2020
DOI: 10.1101/2020.05.28.20116178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Worsening of pre-existing psychiatric conditions during the COVID-19 pandemic

Abstract: This study anonymously examined 2,734 psychiatric patients worldwide for worsening of their pre-existing psychiatric condition during the COVID-19 pandemic. Valid responses mainly from 12 featured countries indicated self-reported worsening of psychiatric conditions in 2/3rd of the patients assessed that was validated through their significantly higher scores on scales for general psychological disturbance, post- traumatic stress disorder, and depression. Female gender, feeling no control of the situation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Although the suicide scale does not have a cut-off point, any score greater than 0 could be considered risky, in the present study there are low scores and almost half of participants have at least suicidal ideation, this result is supported by previous studies that have found that during the COVID-19 pandemic, people with psychological disorders have worsened their condition, which is associated with a higher risk of suicide (Gobbi et al, 2020;Gunnell et al, 2020;Plomecka et al, 2020). Furthermore, as stated by Sheffler et al (2021) in their interpersonal theory of suicide, confinement and pandemic have increased social isolation, the conviction of not being necessary or useful, and the exposure to suffering from losses and deaths.…”
Section: Discussionsupporting
confidence: 82%
“…Although the suicide scale does not have a cut-off point, any score greater than 0 could be considered risky, in the present study there are low scores and almost half of participants have at least suicidal ideation, this result is supported by previous studies that have found that during the COVID-19 pandemic, people with psychological disorders have worsened their condition, which is associated with a higher risk of suicide (Gobbi et al, 2020;Gunnell et al, 2020;Plomecka et al, 2020). Furthermore, as stated by Sheffler et al (2021) in their interpersonal theory of suicide, confinement and pandemic have increased social isolation, the conviction of not being necessary or useful, and the exposure to suffering from losses and deaths.…”
Section: Discussionsupporting
confidence: 82%
“…However, the authors of this cross-sectional study were unable to prove that these findings were a direct result of the pandemic and/or lockdown restrictions [10]. According to the results of another cross-sectional study involving several countries, more than half of the participants who reported a previous mental disorder also stated that their condition had worsened due to the COVID-19 pandemic [11]. In contrast, in our own study conducted in Germany, we found no detrimental effects on the psychological well-being of mentally ill participants four weeks after the implementation of lockdown restrictions, compared to their base levels recorded in surveys before the lockdown [8].…”
Section: Introductionmentioning
confidence: 77%
“…Additionally, among 331 individuals who were abstaining from alcohol pre‐COVID, 18.7% reported a relapse during the pandemic (Sun et al, 2020 ). Finally, in a study of 2734 patients with a variety of mental health conditions, 66% reported a worsening of their psychiatric state (Gobbi et al, 2020 ). The documented worsening of psychological symptoms in those with pre‐existing mental health conditions demonstrates the critical need to investigate exactly how the COVID‐19 pandemic has affected the psychological health of this population subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have focused on how individuals with specific mental health conditions have been affected by the COVID‐19 pandemic, few studies have examined multiple mental health conditions in the same study or compared the impact of the COVID‐19 pandemic across different mental health conditions. Indeed, studies that have considered multiple mental health conditions have combined across diagnoses rather than examine diagnoses separately (e.g., Gobbi et al, 2020 ). Additionally, most studies have relied on quantitative methods to investigate the effects of the COVID‐19 pandemic on psychological health.…”
Section: Introductionmentioning
confidence: 99%